English Phrase Learning With Multimodal Input - Huang, Yuanlin; Zhang, Zina; Yu, Jia; Liu, Xiaobin; Huang, Yuhong (Frontiers in Psychology, 2022)
Though multimodal input has the potential to lead to more sound learning outcomes, it carries the risk of causing cognitive overload, so it is difficult to determine the exact effects of multimodal input on second language (L2) phrase learning. The present study tests the efficacy of multimodal input on L2 phrase learning. The study adopts a mixed-method approach by utilizing both quantitative and qualitative data. The experimental design is a 2×3 mixed model, with Group (the experimental group, and the control group) as the between-subject factor and Time (pretest, midtest, and posttest) as the within-subject factor. 66 participants were divided into two groups. All materials incorporated three aspects of phrase knowledge (form, meaning, use), but the materials of the control group (CG) were unimodal in that they were offered only on paper and of the experimental group (EG) multimodal in that they included pictures, audio recordings and video clips. After the treatment, a questionnaire and a semi-structured interview were given to the EG learners to explore their perceptions of using multimodal materials to learn L2 phrases. The results indicate that both groups had significant gains in learning phrases, but students with the multimodal input achieved significantly better results than those with the unimodal input. Moreover, the EG students had a general positive attitude towards the use of multimodal resources. The present study validates the efficacy of multimodal input on the acquisition of English phrases, and shows that cognitive overload was avoided by sequencing the information.